Religious Pluralism or Conformity in Southeast Asia’s Cultural Legacy - Reid, Anthony (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2015)
In a recently published book, the present author argues that Asia is “the great laboratory of religious pluralism.” The jostling together of mosques, viharas, churches and all kinds of temples has long been a feature of the vibrant cities of Southeast Asia, while anthropologists have celebrated the diversity of its rural people. Yet there is a paradox. At the level of formal religious adherence, Southeast Asia looks to be one of the world’s least diverse regions. This article addresses both the deeper sources of religious tolerance and the modern factors tending, notably in Indonesia, to replace that pattern with one of greater religious conformity. The Indonesian state motto is the epitome of this paradox –Bhinneka Tunggal Ika, ‘They are many, yet they are one.’ The article concludes that while the older tolerance of diversity is indeed under threat today, Southeast Asia’s own traditions should prove a valuable supplement to modern human rights concepts in maintaining the balance.DOI: 10.15408/sdi.v22i3.2352